Effect of γ' particles morphology on dynamic strain aging behavior of Udimet 500 superalloy. (August 2022) - Khani Moghanaki, Saeed; Mohammadi, Hamidreza
Abstract: The Udimet 500 superalloy is a promising candidate material for power plant gas turbine blades due to its excellent mechanical properties at high temperatures. However, dynamic strain aging (DSA) behavior of the Udimet 500 superalloy during high-temperature tensile test has not been investigated so far. In the present study, the effect of γ' particles size and volume fraction on dynamic strain aging behavior of the Udimet 500 superalloy were investigated in the terms of serration frequency and magnitude. The serrated flow was observed in the stress-strain curves during plastic straining at 800 °C. The results illustrated that the γ' particles morphology has significant effect on serration frequency, serration magnitude, and fracture mechanism of the Udimet 500 superalloy. Although, the serration frequency decreased with reducing γ' particles size and increasing γ' particles volume fraction, the serration magnitude increased. The governing mechanism for dynamic strain aging of the Udimet 500 superalloy have been proposed by dislocation interactions with solute atoms and γ' particles. Furthermore, a non-zero work hardening rate is observed during Lüders elongation which was attributed to high volume fraction of γ' particles in precipitation strengthened superalloys. The effect of dynamic strain aging on fracture mechanism was also investigated. When dynamic strain aging was absent, the dimples initiated at the γ/γ' interfaces during room temperature tensile test. Dynamic strain aging inhibits dimples formation at the γ/γ' interfaces. Graphical Abstract: ga1 Highlights: Dynamic strain aging is observed in Udimet 500 superalloy. γ' particles influence the serration frequency and magnitude. Dynamic strain aging mechanism in precipitation strengthened superalloys is proposed. Dynamic strain aging can alter dimples formation mechanism.